The WORMESH-II flatworm-like mesh robot with 2-DOF double joints - Ganegoda V. C. Rasanga; Kengo Hiraishi; Ryuichi Hodoshima; Shinya Kotosaka (ROBOMECH Journal, 2023)
Abstract This paper deals with the development of a flatworm-like mesh robot WORMESH-II, which is the second prototype in the WORMESH series inspired from a flattened and soft-bodied flatworm. The pedal locomotion is the primary locomotor of the flatworm that is continuous gliding propulsion along the bottom of the body. The significance of WORMESH series is use of multiple pedal waves to generate the locomotion. The WORMESH-II is a modular robot having a revolute joint system to interconnect two modules. Further, it contains two module types: control module (CM) and joint module (JM). Depending on their arrangements, WORMESH-II can be arranged in different module formations. First, this paper presents the design of WORMESH-II in which double joints capable of three-dimensional motion are introduced. Then, two locomotion gaits for translational and spinning locomotion are described for WORMESH-II in isotropic module formation. Three synchronized parallel pedal waves and one pedal wave loop by the new double joint mechanism were respectively utilized to generate translational and spinning motions of WORMESH-II for IMF. The proposed locomotion gaits were investigated by dynamics simulation and the experiment using the prototype of WORMESH-II. We have successfully demonstrated basic translational and spinning locomotion of WORMESH-II with the velocity of 2.8 mm/s and the angular velocity of 0.0043 rad/s, respectively.